Comparison of alternative splicing (AS) events in adipose tissue of polled dorset versus small tail han sheep. Issue 4 (April 2023) - Miao, Xiangyang; Luo, Qingmiao; Zhao, Huijing; Qin, Xiaoyu
Abstract: Background: During the alternative splicing (AS), the exons of primary transcripts are spliced in various arrangements, resulting in structurally and functionally distinct mRNAs and proteins. This study aimed to examine genes with AS events from Small Tail Han sheep and Dorset sheep to explore the mechanism of adipose developments. Methods: This study identified the genes with AS events in adipose tissues of two different sheep with next-generation sequencing. In this paper, genes with significantly different AS events were performed gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Results: 364 genes with 411 A S events showed significant differences in adipose tissues between the two breeds; 108 genes with 120 A S events were extremely significant differences between the two breeds. We identified several novel genes that are related with adipose growth and development. The results of KEGG and GO analysis indicated that oocyte meiosis, mitogen-activated protein kinase (Wnt), mitogen-activated protein kinase (MAPK) signaling pathway, etc. Were closely related to the adipose tissue developments. Conclusions: This paper revealed that the genes with AS events are important for adipose tissues in sheep, exploring the mechanisms of AS events associated with adipose tissue developments in sheep of different breeds.